The evolution of amniote gastrulation: the blastopore‐primitive streak transition. (8th February 2017) - Stower, Matthew J.; Bertocchini, Federica
Abstract : In the animal kingdom, gastrulation, the process by which the primary germ layers are formed involves a dramatic transformation in the topology of the cells that give rise to all of the tissues of the adult. Initially formed as a mono‐layer, this tissue, the epiblast, becomes subdivided through the internalization of cells, thereby forming a two (bi‐laminar) or three (tri‐laminar) layered embryo. This morphogenetic process coordinates the development of the fundamental body plan and the three‐body axes (antero‐posterior, dorso‐ventral, and left‐right) and begins a fundamental segregation of cells toward divergent developmental fates. In humans and other mammals, as well as in avians, gastrulating cells internalize along a structure, called the primitive streak, which builds from the periphery toward the center of the embryo. How these morphogenetic movements are orchestrated and evolved has been a question for developmental biologists for many years. Is the primitive streak a feature shared by the whole amniote clade? Insights from reptiles suggest that the primitive streak arose independently in mammals and avians, while the reptilian internalization site is a structure half‐way between an amphibian blastopore and a primitive streak. The molecular machinery driving primitive streak formation has been partially dissected using mainly the avian embryo, revealing a paramount role of the planar cell polarity (PCP) pathway in streak formation. How did the employment of this machinery evolve? The reptilian branch of the amniote clade might provide us with useful tools to investigate the evolution of the amniote internalization site up to the formation of the primitive streak. WIREs Dev Biol 2017, 6:e262. doi: 10.1002/wdev.262 This article is categorized under: Early Embryonic Development > Fertilization to Gastrulation Early Embryonic Development > Gastrulation and Neurulation Comparative Development and Evolution > Body Plan Evolution Abstract : The primitive streak is currently considered as the landmark of amniote gastrulation. However, a close look at gastrulation in reptiles reveals the absence of the primitive streak and the presence of a blastopore slit. We review what is known about gastrulation in the three groups that constitute the amniote clade, reptiles, avians and mammals, and the molecular mechanisms driving this morphogenetic event, with an evolutionary perspective.